Effectiveness of 2020 Airborne Lidar for Identifying Archaeological Sites and Features on Guåhan (Guam). Issue 1 (9th November 2022) - Jalandoni, Andrea; Kottermair, Maria; Dixon, Boyd; Torres, Victor Hara
Guåhan (Guam), part of the Mariana Islands in the western Pacific, has an archaeological record spanning almost four millennia. In this seminal academic paper on the use of lidar for archaeological investigation on Guåhan, we determined which known sites can be visually detected to explore the effectiveness of lidar in this context. Several archaeological site types and features from the Latte, Spanish, and Modern Periods were examined using high-resolution 2020 airborne lidar. We generated the most commonly used digital elevation models (DEMs), which are digital terrain models (DTMs) and digital surface models (DSMs), and visualised them as a hillshade. Lidar proved effective for identifying all the Modern Period sites and most of the Latte and Spanish Period sites, although some features remained obscure. Major challenges and limitations of using lidar on Guåhan were vegetation, site size, and visual ambiguities. While this study used conventional lidar derivatives, it exposed the potential to find more archaeological sites by applying more complex lidar processing techniques in the future. The benefits of lidar are of great interest to the local community, especially the Indigenous CHamoru, interested in non-destructive ways to assist their cultural heritage management.